Events with an isolated lepton and missing transverse momentum and measurement of W production at HERA - Aaron, F; Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Martin, M; Alexa, C; Andreev, V; Antonelli, S; Antonioli, P; Antonov, A; Antunovic, B; et al. (Springer-Verlag, 2010)
Events with high energy isolated electrons, muons or tau leptons and missing transverse momentum are studied using the full e ± p data sample collected by the H1 experiment at HERA, corresponding to an integrated luminosity of 474 pb -1. Within the Standard Model, events with isolated leptons and missing transverse momentum mainly originate from the production of single W bosons. The total single W boson production cross section is measured as 1.14±0.25 (stat.)±0.14 (sys.) pb, in agreement with the Standard Model expectation. The data are also used to establish limits on the WW γ gauge couplings and for a measurement of the W boson polarisation.